2010
DOI: 10.1386/tear.8.2.181_1
|View full text |Cite
|
Sign up to set email alerts
|

Embodied in a metaverse: Anatomia and body parts

Abstract: In this article, the artist/author wishes to examine corporeality in the virtual realm, through the usage of the (non)-physical body of the avatar. Two sister art installations created in the virtual world of Second Life, both of which are meant to be accessed with site-specific avatars, will provide the creative platform whereby this investigation is undertaken. While the installation Anatomia aims to propel the visitor towards reflections of an introverted nature, involving the fragility of the physical sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…When creating their virtual selves, users embody their identities through the construction of their avatars, with the intention to achieve their claimed personality (Ayiter, 2010;Yee et al, 2009). Through their profiles, individuals can share additional information regarding their interests or beliefs, further emphasizing the social aspects of a given identity.…”
Section: Identity Formation In Virtual Worldsmentioning
confidence: 99%
“…When creating their virtual selves, users embody their identities through the construction of their avatars, with the intention to achieve their claimed personality (Ayiter, 2010;Yee et al, 2009). Through their profiles, individuals can share additional information regarding their interests or beliefs, further emphasizing the social aspects of a given identity.…”
Section: Identity Formation In Virtual Worldsmentioning
confidence: 99%
“…Manus ise evli kadınlar üzerinde kurulan egemenliği ifade etmektedir [70] . Roma Hukuku'na ilişkin kaynaklarda manus'a bir nevi evlat edinme gözüyle bakılabileceğine ilişkin ifadeler yer almaktadır [71] . Bu nedenle manus, hukukî işlemden doğan baba egemenliği içerisinde ele alınmaktır.…”
Section: Hukukî İşlemden Doğan Baba Egemenli̇ği̇unclassified
“…Anyone can change the way they look with a few clicks of the mouse (Ananthaswamy, 2007). Ayiter (2010) found that just as people choose their selfrepresentations in virtual environments, their self-representations shaped their behaviors in turn. These changes happen not over hours or weeks, but within minutes.…”
Section: A Number Of Scholars Have Used Berger and Luckmann's Theory mentioning
confidence: 99%